Technologies and Second Language: Nigerian Students’ Adaptive Strategies to Cope With Language Barrier in Northern Cyprus - Elega, Adeola Abdulateef; Özad, Bahire Efe (Journal of International Students, 2017)
This study sought to investigate how Nigerian students in Northern Cyprus cope with language barrier and increase interactions with people of the host community beyond the classroom via utilizing technological adaptive strategies. In order to complete this study, a descriptive design based on a survey conducted among 238 Nigerian students studying in a North Cyprus university was used. Result shows that mobile translation apps such as Google Translate, iVoice translator pro and iTranslate voice mobile were frequently used by Nigerian students more than other technological adaptive strategies. We also found that male students use ICT to cope with language barrier more than the females, and that social media was widely used, second to the translation assistant apps.